2021
DOI: 10.1038/s41467-021-23356-w
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral CXCR5+CD8+T associates with favorable clinical outcomes and immunogenic contexture in gastric cancer

Abstract: Studies that examined an association between CD8+T and prognosis in gastric cancer are inconsistent, and a distinct population of CXCR5+CD8+T associated with better overall survival has been reported among various malignancies. Here, we show that the abundance of intratumoral CXCR5+CD8+T cells is associated with better overall survival in patients with gastric cancer. Patients with TNM II + III gastric cancer with higher intratumoral CXCR5+CD8+T cell infiltration are more likely to benefit from adjuvant chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…Several studies have shown that tumors with a higher TMB can produce more neoantigens, which are more easily recognized by T cells and induce greater immune cytotoxic activity ( Rooney et al, 2015 ). In addition, multiple studies have shown that patients with positive expression of PD-L1 in tumors and infiltration of CD8 + T cells have longer overall survival times ( Wang et al, 2018 ; Wang et al, 2021 ), as was observed in our analysis.…”
Section: Resultssupporting
confidence: 87%
“…Several studies have shown that tumors with a higher TMB can produce more neoantigens, which are more easily recognized by T cells and induce greater immune cytotoxic activity ( Rooney et al, 2015 ). In addition, multiple studies have shown that patients with positive expression of PD-L1 in tumors and infiltration of CD8 + T cells have longer overall survival times ( Wang et al, 2018 ; Wang et al, 2021 ), as was observed in our analysis.…”
Section: Resultssupporting
confidence: 87%
“…It has been reported that intratumoral specific CD8 + T cell biomarkers can determine the prognosis and immunoevasive outcomes in ccRCC patients, which is a probable explanation for why ccRCC tumors progress despite a robust CD8 + T cell infiltration ( 23 , 50 , 51 ). However, the randomly selected markers might not reflect the heterogeneity of CD8 + T cells ( 50 , 51 , 64 ). In this study, WGCNA was used to identify CD8 + T cell related module genes, while the unsupervised clustering method was used to better identify novel CD8 + T cell-related molecular patterns.…”
Section: Discussionmentioning
confidence: 99%
“…While PD-1 blockade combined with immune modulators, such as TGF-β1 inhibitor, might take patients more benefits than targeted PD-1 alone [ 6 ]. And it was also reported that some subsets of CD8+ T, such as CXCR5+CD8+ T [ 8 ], but not CD8+ T itself connected with better overall survival (OS) in patients with GC. Therefore, it is important to find out the key molecules that regulate immune modulators in TME or/and co-express molecular in CD8+ T that mediated its function.…”
Section: Introductionmentioning
confidence: 99%